Transformasi UMKM Digital dalam Mengurangi Pengangguran di Indonesia - Aulia Azzahra; Imahda Khoiri Furqon; Agus Faisal (Journal of Islamic Economic Scholar, 2025)
Unemployment remains one of the major economic challenges in Indonesia. The increasing number of job seekers is not always balanced by the availability of employment opportunities, resulting in a relatively high unemployment rate. At the same time, rapid technological development has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt digital transformation as a strategy to improve business performance and competitiveness. This study aims to examine the role of digital MSME transformation in reducing unemployment in Indonesia. The research employs a descriptive qualitative approach using a literature review method by analyzing relevant books, journals, and government publications. The findings indicate that digital transformation enables MSMEs to expand market reach, improve operational efficiency, and increase business revenue through the use of marketplaces, social media, digital payment systems, and other technological platforms. Furthermore, digitalization creates new employment opportunities in fields such as digital marketing, social media management, online customer service, content creation, and e-commerce administration. The growth of digital MSMEs also promotes entrepreneurship, allowing more individuals to establish businesses and generate employment opportunities. Therefore, digital MSME transformation can serve as an effective solution to reduce unemployment while supporting economic growth and improving community welfare in Indonesia.